Athleticism, politics and media in Greece - Doulkeri, Tessa Doulkeri; Maniou, Theodora; Tsiolcha, Anastasia (Information & Media, 2015)
This paper analyzes the relationship between athletes and politics and especially the case of athletes with active political life in Greece. The study, although begins from a general theoretical framework, focuses on athletes (well-known and/or for their Olympic Achievements) who have been promoted by the media, are well known and have been involved in the Greek political arena. The study begins from the hypothesis that sports, as a cultural factor and vector, participate in the procedure of constructing the collective and social representations and help in shaping the public opinion. In this context, we will investigate the role of the media for the promotion of sports and sports global events, their contribution in constructing sports idols (sports star system, ‘Semi-Gods’, according to Morin, 1972) and some stereotypical attitudes and behaviors. We will conclude by highlighting the political attention given to the sports via the above processes as a factor of exercising political power.